Conservative protestants and engagement with sexual minorities living with HIV: the role of disgust and recategorizing contact - Kang, Ezer (Mental health, religion & culture, 2019)
Conservative Protestants in the United States have historically distanced themselves from gay men, lesbians, and transgender persons living with HIV based largely on fears of moral contamination which are propagated by disgust. We argue how disgust can implicitly reify social divides that engender condemnation and subjugation. However, we will propose that it is achievable to safeguard the traditional tenets of sexuality and gender among conservative Protestants and actively oppose misapplications of those tenets to exclude persons living with HIV. We will support our thesis by describing the work of a medical clinic founded on conservative Protestant ideology that serves hijras and kotis living with HIV in India. We will introduce how applications of recategorizing contact, cognitive consistency, and cultural scaffolding are formative in maintaining one’s ideological integrity without enacting exclusion based on fear and disgust.